Layered metal oxides loaded ceramic membrane activating peroxymonosulfate for mitigation of NOM membrane fouling. (15th August 2022) - Bai, Zhaoyu; Gao, Shanshan; Yu, Huarong; Liu, Xiwen; Tian, Jiayu
Highlights: Layered metal oxides loaded ceramic membrane were successfully fabricated. In-situ PMS activation could mitigate NOM membrane fouling effectively. Surface-bound radical and 1 O2 were idenfied as the dominant ROS. CoAl-LMO was the best activator of PMS for membrane fouling mitigation. Abstract: Catalytic membrane can achieve sieving separation and advanced oxidation simultaneously, which can improve the effluent water quality while reducing membrane fouling. In this study, the catalytic membranes (M 2+ Al@AM) were fabricated by loading different binary layered metal oxides (M 2+ Al-LMO: MnAl-LMO, CuAl-LMO and CoAl-LMO) on alumina ceramic substrate membranes (AM) via vacuum filtration followed by calcination process. The performance of the catalytic membranes was investigated by filtering actual surface water. It was found that the presence of peroxymonosulfate (PMS) could mitigate membrane fouling effectively, as evidenced by the increase of normalized flux from 0.28 to 0.62 in CoAl@AM/PMS system, from 0.25 to 0.52 in CuAl@AM/PMS system, and from 0.22 to 0.31 in MnAl@AM/PMS system, respectively. Correspondingly, the CoAl@AM exhibited the highest removal for UV254, TOC and fluorescent components in the surface water, followed by CuAl@AM and MnAl@AM. Quenching effect of phenol and furfuryl alcohol proposed the surface-bound radicals and singlet oxygen were the major reactive oxygen species in the M 2+ Al@AM/PMS systems. Interface free energy calculations confirmed the in-situ PMS activation could enhance the repulsive interactions between NOM and the membranes, thus mitigating membrane fouling. This work provides an original but simple strategy for catalytic ceramic membrane preparation and new insights into the mechanism of membrane fouling mitigation in catalytic membrane system. Graphical abstract: Image, graphical abstract